Do we still need cryoprecipitate? Cryoprecipitate and fibrinogen concentrate as treatments for major hemorrhage — how do they compare?. Issue 5 (4th May 2018) - Novak, Alex; Stanworth, Simon J.; Curry, Nicola
ABSTRACT: Introduction : Major hemorrhage is a source of significant mortality and morbidity worldwide. Identification and characterization of coagulation impairment associated with major hemorrhage has suggested a key role for fibrinogen deficiency, however the optimum mode of replacement of fibrinogen remains unclear, and standardized major hemorrhage protocols may overlook context-dependent variations in individual patients' clotting derangement. Areas covered : This paper examines the current practice and evidence regarding the role of different modes of fibrinogen replacement in major hemorrhage in 3 distinct clinical settings: trauma, obstetric hemorrhage, and gastrointestinal hemorrhage with associated liver disease. A literature search was carried out electronically using Athens access to the National Health Service evidence health information resources, primarily PubMed and Google Scholar. Expert commentary : Two key questions need to be addressed. First, what is the role of concentrated fibrinogen (by comparison to no fibrinogen), and second, which concentrated source or product is more effective (or cost-effective)? Current practice and concept is derived largely from small pilot trials in the trauma setting, but results from larger studies are awaited. More comparative data on changes to clotting profiles in different groups of bleeding patients are needed to help delineate differences and guide interventional treatment studies.